PENGARUH KUALITAS PELAYANAN PERPAJAKAN, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DI KPP PRATAMA MEDAN BELAWAN - Lubis, Reza Hanafi (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2017)
This research is to measure the influence of service quality at KPP Pratama Medan Belawan and tax sanctions. This research using survey with description quantitative. These samples are 100 tax payers at KPP Pratama Medan Belawan. The questionaires are for the tax payers as respondence. The results service quality and tax sanction have positive influence for the tax payers obidient at KPP Pratama Medan Belawan.Keywords: service quality, sanction, obedient